Effect of silver diamine fluoride on plaque microbiome in children. Issue 3 (May 2020) - Mei, May Lei; Yan, Zejun; Duangthip, Duangporn; Niu, John Yun; Yu, Ollie Yiru; You, Meng; Lo, Edward C.M.; Chu, Chun Hung
Abstract: Objective: To investigate the microbiome profile and relative abundance changes of the plaque on silver diamine fluoride (SDF)-treated caries in children with early childhood caries. Methods: A single trained examiner assessed the caries as being arrested or active and then collected plaque samples from the caries lesions from fourteen 5-year-old children immediately before, 2 weeks after, and 12 weeks after a one-off application of 38 % SDF. We assigned 16S rRNA gene sequences to operational taxonomic units (OTUs) using a 98.5 % identity cut-off. We also used a variety of taxonomy- and phylogeny-based statistical approaches to compare the biodiversity and relative abundance among different groups. Results: The caries arrest rate were 90 % and 83 % after 2 and 12 weeks, respectively. We studied 46 plaque samples and identified 388 OTUs (254 identified at the species level, 129 identified at the genus level, and 76 identified at the family level). There was no significant change in the diversity in the arrested caries before and 12 weeks after SDF treatment (p = 0.71). The diversity in active caries reduced significantly 12 weeks after SDF treatment (p = 0.006). The relative abundance of certain caries-related species (e.g., Streptococcus mutans and Lactobacillus sp .) was reduced in arrested caries but was increased in active caries after SDF treatment. Conclusion: There was no overall microbiome changes in the caries arrested by SDF. The relative abundance of some caries-related species is reduced in arrested caries, while increased in active caries. Clinical significance: This study provides information on microbiome changes on SDF-treated caries of children.